A new subgenus and species of the genus Hedyphanes Fischer von Waldheim, 1820 (Coleoptera: Tenebrionidae: Helopini) from Israel and Egypt - Nabozhenko, Maxim V.; Lillig, Martin (Zootaxa, 2013)
A new species, Hedyphanes chikatunovi sp. n., is described from southern Israel (Negev, Gerofit) and Egypt (Northern Sinai). These localities represent the southwestern limit of the distribution of the genus. The new species is placed in a new monotypic subgenus, Microhedyphanes subgen. n.